Current account deficit problems in developing countries: a comparative analysis - Bektaşoğlu, Yunus (My University, 2013)
Cari işlemler dengesi son yüzyılın iktisat literatüründe tartışılan en önemli konulardan biridir. Yüksek cari açıklarının temel nedenlerini anlamak için yıllar boyunca üç temel yaklaşım tartışılmıştır. Esneklik yaklaşımı yerel paranın değersizleşmesinin ticaret dengesi üzerindeki etkisine odaklanır. Massetme yaklaşımı cari açığı milli geliri aşan bir harcama düzeyinin sonucu olarak görür. Parasal yaklaşım cari açığı parasal bir olgu görmesiyle diğer iki Keynesyen yaklaşımdan ayrılır. Bu çalışmada hangi yaklaşımın cari açığı daha iyi açıkladığını anlamak için üç temel yaklaşım analiz edilmiştir. Bu üç yaklaşımın temel varsayımlarına dayanarak gelişmekte olan ülkeler için panel veri analizi ile üç model test edilmiştir. Analizde yer alan gelişmekte olan ülkeler Arjantin, Brezilya, Hindistan, Endonezya, Malezya, Meksika, Filipinler, Güney Afrika, Tayland ve Türkiye’dir. Ampirik sonuçlara göre esneklik ve massetme yaklaşımları cari açıkların nedenlerini açıklamada yetersiz bulunurken parasal yaklaşım açıkların nedenlerini belirlemekte açıklayıcı yaklaşım olarak bulunmuştur. Cari Açık, Esneklik Yaklaşımı, Massetme Yaklaşımı, Parasal Yaklaşım, Panel Veri Analizi

The concept of current account deficit is a very prominent topic which has been discussed for the last century in economic literature. In order to determine the main causes of the high current account deficits, three main approaches: elasticity, absorption and monetary approach have been discussed throughout the years. Elasticity approach focuses on the impact of the currency depreciation on trade balance. Absorption approach considers the current account deficit as an outcome of excess expenditure over national output. Monetary approach differs from the previous Keynesian approaches by considering the current account deficits as a monetary phenomenon. In this study, three basic approaches to the balance of payments are analyzed to understand which approach is better to explain reasons of current account deficits in developing countries. On the basis of basic assumptions of these approaches, three models are tested by employing panel data analysis for ten developing countries: Argentina, Brazil, India, Indonesia, Malaysia, Mexico, Philippines, South Africa, Thailand and Turkey. According to the results of these three models, elasticity approach and absorption approaches are found insufficient while monetary approach to the balance of payments is found acceptable to explain the real causes of deficits. Current Account Deficit, Elasticity Approach, Absorption Approach, Monetary Approach, Panel Data Analysis
Keywords: Ekonomi; Keynes Ekonomisi